Child health, household environment, temperature and rainfall anomalies in Honduras: a socio-climate data linked analysis - Cristina Bradatan; Jeffrey A. Dennis; Nadia Flores-Yeffal; Sharmistha Swain (BMC, 2020)
Abstract Background As climate research continues to highlight the global shifts in temperature and precipitation, more research is needed to understand how climate anomalies impact human health outcomes. In this paper, we analyze one of the paths through which climate anomalies affect health (in particular, child's health) within one of poorest countries in the world (Honduras). Methods Using the GPS location of the household, we link information on child health and house amenities from the Honduras Demographic Health Survey 2011-2012 dataset (a nationally representative sample) with climate data (1981-2012) from the Climate Research Unit (CRU TS3.21). We use generalized estimating equations for binary logistic models and spatial association to analyze these data. Results We show that 1) areas experiencing significant temperature anomalies are also the ones with the worst child respiratory problems and 2) in households with poor amenities - such as access to sanitation and clean water, children tend to have a high incidence of respiratory diseases and diarrhea . Conclusions We conclude that, as climate change increases the incidence of climate anomalies, tackling in advance those household environmental factors responsible for poor child health outcomes (better sanitation and clean cooking fuel) can prevent a further deterioration of children's health in Honduras.